The challenges faced by nurses in promoting and maintaining exclusive breastfeeding (Research, Society and Development, 2025)
Exclusive breastfeeding until six months of age is an essential practice recommended by the World Health Organization and the Ministry of Health, as it provides all the nutrients necessary for child growth and development, in addition to strengthening the bond between mother and child. Despite scientific evidence proving its benefits, adherence rates to exclusive breastfeeding are still lower than the targets set by health agencies, due to sociocultural, emotional, and institutional factors that hinder its practice. In this context, nurses play a fundamental role in promoting, encouraging, and maintaining breastfeeding, acting from prenatal care to the postpartum period. Objective: To analyze, in the scientific literature, the challenges faced by nurses in promoting and maintaining exclusive breastfeeding, as well as the strategies used to overcome them. Methodology: This is a qualitative, descriptive, bibliographic review study, based on scientific publications available in the Virtual Health Library (VHL) database. Articles published between 2015 and 2025, in Portuguese, English, or Spanish, were included. Results and discussion: The results showed that, although exclusive breastfeeding is widely recognized, its adherence is hampered by physiological, emotional, sociocultural, and institutional factors. The nurse acts as an essential agent by offering educational actions, emotional support, and technical guidance to breastfeeding mothers. Final considerations: The humanized and educational role of nursing is indispensable to strengthen maternal self-confidence and increase exclusive breastfeeding rates, making investment in training, adequate infrastructure, and supportive public policies essential.